Porous pva-sa-mbf composite bio-carriers for embedding anammox bacteria, preparation method thereof and application thereof in high-salt nitrogen-containing wastewater

CN122979293APending Publication Date: 2026-10-27SHANGHAI YIKE GREEN ENG +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611287505.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]综上,目前尚缺乏一种集高传质、高机械强度、高生物活性于一体的复合包埋生物填料

Benefits of technology

1、本申请在包埋混合胶液中加入碳酸氢钠,滴球成型过程中会产生大量CO2气泡,从而在多孔PVA-SA-MBF复合生物填料内部形成孔径为20-200μm的宏观多孔结构,为营养物质和气体的传递提供了高效通道,利于底物供给和代谢产物排出,可有效解决PVA包埋体传质阻力大的问题,提高内部Anammox菌的底物可及性和活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979293A_ABST
    Figure CN122979293A_ABST
Patent Text Reader

Abstract

The application discloses embedded anaerobic ammonia oxidation bacteria porous PVA-SA-MBF composite biological filler and a preparation method and application thereof, and the preparation method comprises the following four steps: S a , preparing iron-carbon modified basalt fiber MBF; S b , preparing embedded mixed glue solution; S c , drop ball forming and cross-linking curing; S d , cleaning and activating. The design of the embedded matrix + reinforcing fiber + porous structure has a synergistic effect: the embedded matrix PVA-SA composite gel provides a physical embedding barrier to prevent Anammox bacteria from flowing out; the reinforcing fiber MBF enhances the mechanical strength of the particles and promotes microbial enrichment; the porous structure ensures efficient substrate transmission; the three are synergistic, realizing the unity of "high biomass retention, high mass transfer efficiency and high biological activity". The embedded anaerobic ammonia oxidation bacteria porous PVA-SA-MBF composite biological filler can effectively treat nitrogen-containing industrial wastewater with a salinity of 35 g / L, is suitable for treating high-salt complex wastewater, and expands the application range of the anaerobic ammonia oxidation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of nitrogen-containing wastewater treatment technology, and more specifically, to a porous PVA-SA-MBF composite biological packing material for encapsulating anaerobic ammonia-oxidizing bacteria, its preparation method, and its application in high-salt nitrogen-containing wastewater. Background Technology

[0002] High ammonia nitrogen wastewater, such as pharmaceutical wastewater, marine aquaculture wastewater, and some chemical wastewater, usually also has relatively high salinity. Traditional biological denitrification processes often face problems such as inhibited bacterial communities, decreased denitrification efficiency, and increased operating costs in the treatment of such wastewater. Therefore, developing efficient, low-carbon, and economical denitrification technologies for high-salinity nitrogen-containing wastewater is of great practical significance.

[0003] Anammox is a novel biological nitrogen removal pathway in which autotrophic microorganisms directly denitrify NH4+ under anaerobic conditions. + Electron donor, NO2 - Anaerobic ammonia oxidation (AAM) acts as an electron acceptor, converting nitrogen into nitrogen (N2). Compared to traditional nitrogen removal processes, AAM has significant advantages, including no need for an external organic carbon source, saving approximately 62.5% of oxygen supply energy, and producing only about 8% of the sludge required by traditional processes. The generation cycle of AAM bacteria is as long as 10-13 days, and their proliferation rate is extremely slow, only increasing when the cell density reaches 10¹. 0 Anaerobic ammonia-oxidizing bacteria only exhibit activity when their cell count is above 1% / mL. They have stringent requirements for growth environment, are easily lost with water flow, and their activity is easily inhibited in high-salinity, low-temperature, or highly toxic wastewater. High-salinity nitrogen-containing wastewater (salinity >1% w / v) disrupts osmotic balance, leading to cell dehydration and lysis, inhibiting the activity of key enzymes such as nitrogen metabolism and the TCA cycle. This makes it difficult for anaerobic ammonia-oxidizing bacteria to maintain their natural salt tolerance mechanism, severely restricting the stable operation of autotrophic denitrification processes.

[0004] Immobilization technology, by directly immobilizing high concentrations and high activity of Anammox bacteria within a carrier, effectively prevents microbial loss and maintains high biomass within the reactor. Polyvinyl alcohol (PVA) and sodium alginate (SA) are commonly used immobilization materials. PVA has high mechanical strength but poor mass transfer performance, while SA has good mass transfer performance but insufficient mechanical strength. Although PVA-SA composites improve both aspects, mass transfer resistance remains a key bottleneck restricting the denitrification efficiency of immobilized particles. Studies have shown that the effective mass transfer coefficient of PVA immobilized bodies is only 0.089 mm² / h, far lower than the 0.139 mm² / h of SA immobilized bodies, and the dense "shell" formed on the surface of PVA immobilized bodies severely hinders the transport of nutrients and metabolites.

[0005] In summary, there is currently a lack of composite encapsulation biological fillers that integrate high mass transfer, high mechanical strength, and high biological activity. Summary of the Invention

[0006] In view of the shortcomings of the existing technology, the purpose of this application is to provide a composite encapsulated biological packing material that integrates high mass transfer, high mechanical strength and high biological activity, thereby improving the treatment efficiency of high-salt nitrogen-containing wastewater.

[0007] Basalt fiber (BF), as a novel biological carrier material, possesses excellent biocompatibility and microbial loading capacity, enabling it to rapidly enrich large amounts of activated sludge to form a "microbial nest." Modified basalt fiber (MBF) is obtained by iron-carbon modification of BF. Its weakly positive surface potential allows for the rapid adsorption of negatively charged microorganisms, and micro-electrolysis facilitates the targeted enrichment of salt-tolerant Anammox bacteria. This application introduces MBF into PVA-SA and simultaneously uses an extracellular polymeric substance (EPS) aqueous solution to prepare an encapsulation mixture. This enhances the activity of Anammox bacteria, improves their mass transfer, and the EPS provides protection in the cross-linking solution, increases microbial adhesion, and preserves maximum microbial activity.

[0008] In a first aspect, this application provides a method for preparing a porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia-oxidizing bacteria, comprising the following steps: S a Preparation of iron-carbon modified basalt fiber (MBF); S b Preparation of embedding mixture S b 1. Weigh out 6%-10% polyvinyl alcohol (PVA), 0.5%-2% sodium alginate (SA), 0.1%-0.5% sodium bicarbonate (SB), and the remainder of an aqueous solution of extracellular polymeric substances (EPS) by mass percentage. S b 2. Step S b The substance weighed in step 1 is stirred and heated to 90-100℃ to dissolve; S b 3. Cool to 30-40℃, then add step S. a The iron-carbon modified basalt fiber MBF obtained in the process was mixed with a solution, and the amount of iron-carbon modified basalt fiber MBF added was 2%-8% of the total mass of polyvinyl alcohol (PVA) and sodium alginate (SA). S b 4. Add the pretreated sludge to step S. b 3. An embedded mixed solution is obtained from the prepared mixture, wherein the mass ratio of the pretreated bacterial mud to the mixed solution is 1:4-10; S c Droplet molding and cross-linking curing S c1. Dissolve 1%-2% calcium chloride in deionized water according to the mass ratio to obtain the first crosslinking solution; dissolve 3%-5% boric acid, 2%-5% calcium chloride and 0.5%-2% ferric chloride in deionized water according to the mass ratio to obtain the second crosslinking solution; S c 2. After pre-crosslinking for 5-10 minutes by dripping the embedded mixed adhesive solution into the first crosslinking agent solution, transfer it to the second crosslinking solution and crosslink in a sealed, light-protected environment at a temperature of 4-10℃ for 12-24 hours to obtain the embedded particles; S d Cleaning and activation After cleaning, the embedded particles were placed in a constant temperature incubator and activated at 30-35℃ for 7-14 days to obtain the porous PVA-SA-MBF composite biological packing material containing anaerobic ammonia oxidizing bacteria.

[0009] Preferably, step S a include: S a 1. After pretreatment and etching, the basalt fibers are ground and sieved, then soaked in an iron salt solution for 6-12 hours at a temperature of 50-90℃. S a 2. Step S a The obtained basalt fibers were soaked in sodium p-toluenesulfonate solution, pyrrole monomer was added, followed by iron salt solution, and the reaction was carried out at room temperature for 12-24 h. The mass ratio of basalt fibers, sodium p-toluenesulfonate, pyrrole monomer, and ferric iron was 5.0:9.7-10.8:3.4-4.2:5.5-6.6. S a 3. The basalt fibers obtained in step S2 are calcined in stages, wherein... First stage: Raise the temperature to 180-220°C and maintain the temperature for 25-40 minutes. Second stage: Raise the temperature to 350-400°C and maintain the temperature for 80-100 minutes. Third stage: Raise the temperature to 510-560°C and keep it warm for 100-130 minutes.

[0010] Preferably, the extracellular polymeric substance (EPS) aqueous solution is prepared by mixing extracellular polymeric substance (EPS) and deionized water at a volume ratio of 1:1, and the extracellular polymeric substance (EPS) is the supernatant extracted by centrifugation after heating anaerobic ammonia oxidizing bacteria.

[0011] Preferably, step S c 2 also includes controlling the dropping rate to ensure that the particle size of the prepared embedded particles is 3-8 mm.

[0012] Secondly, this application provides a porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia-oxidizing bacteria, prepared by the above-described method, comprising: Embedding matrix: a composite gel of polyvinyl alcohol (PVA) and sodium alginate (SA); Iron-carbon modified basalt fiber (MBF): dispersed in the embedded matrix; Anaerobic ammonia-oxidizing bacteria: embedded in the embedding matrix.

[0013] Preferably, the iron-carbon modified basalt fiber has a porosity of 90%-93%, a density of 1.03-1.15 g / cm³, and a surface Zeta potential of 10-20 mV.

[0014] Thirdly, this application provides a method for constructing an anaerobic ammonia oxidation biological filter suitable for high-salt nitrogen-containing wastewater, comprising: The above-mentioned porous PVA-SA-MBF composite biological packing material containing anaerobic ammonia oxidizing bacteria is filled into an anaerobic ammonia oxidizing biological filter. The anaerobic ammonia oxidizing biological filter is an upflow biological filter. The volume filling ratio of the porous PVA-SA-MBF composite biological packing material containing anaerobic ammonia oxidizing bacteria is 20%-50%.

[0015] Fourthly, this application provides an anaerobic ammonia oxidation biological filter suitable for high-salt nitrogen-containing wastewater, which is constructed using the above-described construction method.

[0016] Fifthly, this application provides the application of the above-mentioned porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia oxidizing bacteria or the anaerobic ammonia oxidizing biological filter suitable for high-salt nitrogen-containing wastewater in the treatment of high-salt nitrogen-containing wastewater, wherein the sodium chloride content in the high-salt nitrogen-containing wastewater is 10-35 g / L.

[0017] Sixthly, this application provides a method for treating high-salinity nitrogen-containing wastewater, comprising: passing the high-salinity nitrogen-containing wastewater into the above-mentioned anaerobic ammonia oxidation biological filter suitable for high-salinity nitrogen-containing wastewater, and controlling the operating temperature of the anaerobic ammonia oxidation biological filter to be 25-35℃, the pH to be 7.2-8.5, and the hydraulic retention time to be 8-12h.

[0018] The technical solution of this application achieves the following technical effects: 1. This application adds sodium bicarbonate to the embedding mixture, which generates a large number of CO2 bubbles during the droplet forming process. This forms a macroscopic porous structure with a pore size of 20-200 μm inside the porous PVA-SA-MBF composite biological filler, providing an efficient channel for the transfer of nutrients and gases, facilitating substrate supply and metabolic product discharge. This effectively solves the problem of high mass transfer resistance in PVA embedding bodies and improves the substrate accessibility and activity of Anammox bacteria inside.

[0019] 2. Iron-carbon modified basalt fiber (MBF) achieves multiple strengthening effects. MBF has a high porosity of 90%-93% and a density close to that of water (1.03-1.15 g / cm³). 3 It is easily suspended in water, which is conducive to the accumulation of microorganisms on its surface. Its weak positive surface potential (Zeta potential 10-20mV) can quickly adsorb negatively charged microorganisms. The iron-carbon micro-electrolysis can directionally enrich salt-tolerant functional bacteria, so that the porous PVA-SA-MBF composite biological packing material with embedded anaerobic ammonia oxidizing bacteria can still maintain high denitrification activity in high salinity wastewater. MBF effectively compensates for the strength loss caused by the porous structure by enhancing the interfacial bonding force with the composite gel matrix and bridging and preventing cracking inside the particles, so that the porous PVA-SA-MBF composite biological packing material with embedded anaerobic ammonia oxidizing bacteria has high mechanical strength.

[0020] 3. Ferric chloride is additionally added to the crosslinking solution in this application. On the one hand, Fe³⁺ + It can undergo a stronger cross-linking reaction with sodium alginate, enhancing the gel network structure while matching and enriching the original Fe sites of MBF, thus enhancing the conductive structure; on the other hand, trace amounts of iron ions can serve as micronutrients for microbial growth, promoting the metabolic activity of Anammox bacteria.

[0021] 4. The design of this application, combining the embedding matrix, reinforcing fibers, and porous structure, exhibits a synergistic effect: the PVA-SA composite gel provides a physical embedding barrier to prevent Anammox bacteria loss; MBF enhances the mechanical strength of the particles and promotes microbial enrichment; and the porous structure ensures efficient substrate transport. These three elements work synergistically to achieve a balance of "high biomass retention, high mass transfer efficiency, and high biological activity." Specifically, the porous PVA-SA-MBF composite biological packing material prepared in this application for embedding anammox bacteria can maintain an extremely high local cell concentration of anammox bacteria (up to 10⁻⁶). 9 -10¹ 0 The number of particles per mL is significantly higher than that of suspended sludge systems. The porous structure formed by in-situ foaming with sodium bicarbonate increases the pore size of the embedded particles from the initial 10 μm to 50-80 μm. Combined with the high porosity of MBF (90%-93%), this significantly reduces the mass transfer resistance of substrates and metabolites, resulting in a significant increase in nitrogen removal rate (NRR) and a much shorter reactor start-up time compared to suspended sludge systems. Furthermore, the directional enrichment function of MBF gives the Anammox bacterial community in the embedded particles stronger salt tolerance, enabling effective treatment of nitrogen-containing industrial wastewater with a salinity of up to 35 g / L. This makes it suitable for treating complex high-salt wastewater and expands the application range of anaerobic ammonia oxidation processes.

[0022] 5. During the foaming process of sodium bicarbonate, the water and carbon dioxide produced can dilute boric acid. At the same time, the porous structure greatly improves the mass transfer efficiency, allowing the crosslinking agent molecules (B(OH)4) to...- It can diffuse rapidly and uniformly into the interior of the particles, thus allowing for full cross-linking at lower boric acid concentrations, reducing the amount of boric acid used, and consequently reducing the damage of boric acid to the encapsulated microorganisms.

[0023] The following will further explain the concept, specific structure and technical effects of this application in conjunction with the accompanying drawings, so as to fully understand the purpose, features and effects of this application. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia-oxidizing bacteria in this application.

[0025] Figure 2 This is a schematic diagram illustrating the application of porous PVA-SA-MBF composite biological packing material containing anaerobic ammonia oxidizing bacteria in an anaerobic ammonia oxidation biological filter. Detailed Implementation

[0026] The following specific examples illustrate the implementation of this application. Those skilled in the art can easily understand other advantages and effects of this application from the content disclosed in this specification. This application can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of this application. It should be noted that, unless otherwise specified, the following embodiments and features in the embodiments can be combined with each other.

[0027] Some exemplary embodiments of this application have been described for illustrative purposes. It should be understood that this application may be implemented in other ways not specifically shown in the accompanying drawings.

[0028] The preparation method of the porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia-oxidizing bacteria in this application includes the following four steps: S a Preparation of iron-carbon modified basalt fiber MBF; S b Preparation of embedding mixture; S c Droplet molding and cross-linking curing; S d Cleaning and activation. Each step is described in detail below.

[0029] Step 1: Preparation of Iron-Carbon Modified Basalt Fiber (MBF) Before iron modification of basalt fibers, pretreatment and etching are performed. The purpose of pretreatment is to remove the original adhesives and impurities on the surface of the basalt fibers. Specifically, the pretreatment method involves immersing the basalt fibers in acetone solvent and heating to 38-42°C for at least 1 hour. After pretreatment, drying is preferred. The drying temperature is not limited in this application, as long as the cleaning solvent is no longer adhering to the surface of the basalt fibers.

[0030] The etching process is performed after pretreatment. The purpose of etching is to increase the surface roughness of the basalt fibers, thereby improving the subsequent loading capacity of modified materials. Specifically, the etching method involves placing the pretreated basalt fibers in an etching solution at 20-90°C for 1-24 hours. The etching solution includes one or more of hydrochloric acid, sulfuric acid, hydrogen peroxide, and sodium hydroxide solutions. In one specific embodiment, the etching process includes first placing the pretreated basalt fibers in hydrochloric acid, sulfuric acid, or sodium hydroxide solution at 20-90°C for 2-24 hours, followed by placing them in hydrogen peroxide solution at 40-90°C for 1-12 hours. Treating the basalt fibers with hydrochloric acid, sulfuric acid, or sodium hydroxide solution increases their surface defects. Subsequent immersion in hydrogen peroxide increases the Si-O groups on the basalt fiber surface, enabling the subsequent loading of organic polymer carbon materials onto its surface. The subsequent high-temperature calcination and carbonization to create a porous structure is beneficial for the enrichment and growth of microorganisms.

[0031] Subsequently, the pretreated and etched basalt fibers are ground and sieved to ensure a more adequate load on the subsequent modified materials. Grinding sieves of 140 mesh, 170 mesh, 200 mesh, 230 mesh, etc. can be selected.

[0032] The iron modification method involves immersing ground and sieved basalt fibers in an iron salt solution for 6-12 hours to physically deposit and load iron. The immersion temperature is 50-90℃. In this application, the iron salt solution is a ferric chloride solution, and its concentration is not limited, as long as it can submerge the basalt fibers and achieve iron loading. Preferably, the concentration is above 1M. After the reaction is complete, the fibers are washed with deionized water and dried to obtain iron-modified basalt fibers (Fe-MBF).

[0033] The method for modifying basalt fiber with organic polymer carbon materials is as follows: The iron-modified basalt fiber (Fe-MBF) prepared above is immersed in a sodium p-toluenesulfonate solution, followed by the addition of pyrrole monomer and then an iron salt solution. The reaction is carried out at room temperature for 12-24 hours to prepare iron-modified basalt particles via chemical oxidative polymerization. In this step, the mass ratio of basalt fiber, sodium p-toluenesulfonate, pyrrole monomer, and ferric iron is 5.0:9.7-10.8:3.4-4.2:5.5-6.6. After the reaction is complete, the basalt fiber is washed and purified with deionized water and ethanol to remove impurities and unloaded materials, and then dried in an oven at 60-70℃.

[0034] The basalt fibers modified with iron and organic polymer carbon materials were then subjected to a calcination step in a nitrogen atmosphere. The calcination was carried out using a segmented calcination method. First stage: Low-temperature pre-calcination (room temperature to 180-220°C, heating rate 4-6°C / min, holding time 25-40min) to remove moisture, volatile organic compounds or other impurities from the raw materials and avoid side reactions in the medium and high temperature stages; The second stage: medium temperature reaction (raising the temperature to 350-400°C, heating rate 2-4°C / min, holding for 80-100min) promotes the initial reaction between the metal and the carbon source to form precursors or intermediate products, while avoiding excessive temperature that could lead to runaway reaction. The third stage: high-temperature carbonization (temperature rises to 510-560°C, heating rate 1-3°C / min, holding for 100-130 min). The carbonization reaction is completed at this temperature to generate the target carbide and optimize the crystal structure and product properties.

[0035] The iron-carbon modified basalt fibers prepared in this application have a porosity of 90%-93% and a density of 1.03-1.15 g / cm³. This porosity originates from the microporous structure formed during fiber calcination, with pore sizes primarily consisting of nano-sized mesopores (mainly distributed in the 10-150 nm range). The high porosity and low density facilitate suspension, which is beneficial for microbial accumulation and growth on the surface, enabling the enrichment and cultivation of anaerobic ammonia-oxidizing bacteria. Iron, as a basic substrate and potential energy source, plays a crucial role in the metabolism of anaerobic ammonia-oxidizing bacteria. In the presence of insoluble electron acceptors or electrodes, pre-enriched anaerobic ammonia-oxidizing bacteria can achieve nitrite-free electroactive ammonia oxidation through extracellular electron transfer, while the conductive carrier promotes biofilm formation and granulation processes in anaerobic ammonia-oxidizing bacteria. Polypyrrole (PPy) possesses advantages such as good biocompatibility, excellent electrical conductivity, high thermal conductivity, environmental stability, non-toxicity, high porosity, ease of synthesis, and low cost. Furthermore, PPy exhibits reversible transitions between charged and neutral forms, which is more conducive to the adsorption and accumulation of microorganisms on its surface. More detailed steps for the preparation of iron-carbon modified basalt fiber (MBF) can be found in patent CN120398262A.

[0036] Step 2: Preparation of the embedding mixture Weigh out 6%-10% polyvinyl alcohol (PVA), 0.5%-2% sodium alginate (SA), 0.1%-0.5% sodium bicarbonate (SB), and the remainder is an aqueous solution of extracellular polymeric substances (EPS). The EPS aqueous solution is prepared by mixing EPS and deionized water at a volume ratio of 1:1. The EPS is obtained by heating (preferably 80°C for 2 hours) with anaerobic ammonia-oxidizing bacteria, followed by centrifugation (preferably 8000 rpm for 30 minutes) to extract the supernatant.

[0037] The extracellular polymeric substance (EPS) added in this step plays multiple synergistic and crucial roles: in the subsequent cross-linking and curing stage, EPS acts as a natural polymeric barrier secreted by microorganisms, and its highly hydrated gel network and abundant functional groups (carboxyl groups, hydroxyl groups, etc.) can effectively buffer the high concentration of salt ions (Ca²⁺) in the cross-linking solution. + Fe³ +The chemical and osmotic pressure shocks from boric acid and other substances help Anammox bacteria adapt to the external chemical environment by complexing and adsorbing harmful substances and slowing their diffusion rate to the cell surface, thus ensuring a high survival rate of the bacteria during the high-intensity cross-linking process. At the same time, the polysaccharide and protein components of EPS act as "bio-glue," mediating the firm binding of cells to the PVA-SA gel carrier and MBF through electrostatic attraction, hydrogen bonding, and other interactions. The three-dimensional network formed by EPS interpenetrates and interweaves with the embedded backbone, creating a dual fixation effect that significantly enhances the adhesion stability of microorganisms inside the particles and effectively prevents the loss of the bacterial population. In addition, EPS can act as a "nutrient pool" to capture and enrich substrates during subsequent operation, significantly promoting the aggregation of Anammox bacteria and the formation of biofilms. Some of its components can also act as electron shuttles to participate in extracellular electron transfer, thereby maintaining extremely high local cell concentration and metabolic activity inside the embedded particles, significantly improving denitrification efficiency.

[0038] Subsequently, the weighed substances were stirred and heated to 90-100°C to dissolve.

[0039] Next, the mixture is cooled to 30-40℃, and the iron-carbon modified basalt fiber MBF obtained in step one is added to obtain a mixture. The amount of iron-carbon modified basalt fiber MBF added is 2%-8% of the total mass of polyvinyl alcohol PVA and sodium alginate SA.

[0040] Finally, the pretreated bacterial sludge was added to the prepared mixture to obtain the encapsulation mixture solution, wherein the mass ratio of the pretreated bacterial sludge to the mixture solution was 1:4-10. The pretreatment of the bacterial sludge was as follows: the sludge in the anaerobic ammonia oxidation reactor that had been running stably in the laboratory for a long time was taken out, and it was repeatedly washed three times with phosphate buffer solution with a pH of 7.0 to remove surface impurities. After centrifugation at 4000 rpm for 10-15 min at 5℃, the bacterial sludge was collected, which is the pretreated bacterial sludge.

[0041] Step 3: Droplet Forming and Cross-linking Curing According to the mass ratio, 1%-2% calcium chloride is dissolved in deionized water to obtain the first crosslinking solution; according to the mass ratio, 3%-5% boric acid, 2%-5% calcium chloride and 0.5%-2% ferric chloride are dissolved in deionized water to obtain the second crosslinking solution.

[0042] Pre-crosslink the embedding mixture by dripping it into the first crosslinking solution for 5-10 minutes. Specifically, the embedding mixture is dripped into the crosslinking agent in droplet form using a peristaltic pump or syringe for pre-crosslinking. The dripping rate is controlled to ensure that the prepared embedded particles have a particle size of 3-8 mm. Alternatively, the particles can be custom-sized using a mold, frozen and formed, and then added to the first crosslinking solution for crosslinking for 5-10 minutes to allow the outer shell layer to initially gel. This step utilizes calcium chloride and sodium alginate for rapid ionic crosslinking. + It will replace Na on the SA molecular chain +With the carboxyl group (-COO) on the G unit - The formation of coordinate bonds allows the added droplets to quickly solidify and form a preliminary spherical framework, preventing particle deformation or adhesion during subsequent operations. The specific reaction equation is: 2SA-COO - + Ca² + → (SA-COO)2Ca.

[0043] After pre-crosslinking for 5-10 min, the particles were transferred to a second crosslinking solution and crosslinked in a sealed, light-protected environment at 4-10°C for 12-24 h to obtain embedded particles. During the crosslinking process, sodium bicarbonate reacted with boric acid to generate CO2 gas, forming a macroscopic porous structure with a pore size of 20-200 μm inside the particles, exhibiting obvious honeycomb pores, which is beneficial for the mass transfer of substrates and metabolites. Furthermore, the Ca²⁺ in the second crosslinking solution... + Fe³ + Boric acid and sodium alginate and polyvinyl alcohol, respectively, undergo cross-linking reactions to jointly construct a PVA-boronic ester covalent cross-linked network and SA-Ca²⁺. + SA-Fe³ + The specific reaction formula for the composite crosslinking system with synergistic enhancement of dual ionic crosslinking networks is as follows: 3 SA-COO - + Fe³ + → (SA-COO)3Fe 2 PVA-OH + B(OH)4 - (PVA-O)2B(OH)2 - + 2 H2O.

[0044] Step 4: Cleaning and Activation The cross-linked embedded particles were rinsed repeatedly with phosphate buffer (pH 7.0) and deionized water 2-4 times to remove the residual cross-linking solution on the surface.

[0045] The cleaned embedded particles were placed in a constant temperature incubator and activated at 30-35℃ for 7-14 days, with NH4 added to the water. + -N and NO2 - With a concentration of 20 mg / L for each of the -N groups, the activity of anaerobic ammonia oxidizing bacteria was restored, resulting in a finished porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia oxidizing bacteria.

[0046] The porous PVA-SA-MBF composite biological packing material (particle size 3-8 mm) for embedding anaerobic ammonia-oxidizing bacteria prepared by the above method comprises: an embedding matrix: a composite gel of polyvinyl alcohol (PVA) and sodium alginate (SA); iron-carbon modified basalt fiber (MBF): dispersed in the embedding matrix; and anaerobic ammonia-oxidizing bacteria, embedded in the embedding matrix. The mechanical strength of this composite biological packing material is 1200-2600 g, and the particle integrity rate is >80% after stirring at 600 rpm for 48 h.

[0047] Example 1: Preparation of porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia-oxidizing bacteria Step 1: Preparation of iron-carbon modified basalt fiber (MBF) (1) Basalt fibers were pretreated by heating and refluxing acetone at 60°C for 48 h to remove the sizing agent and impurities from the fiber surface; (2) The pretreated basalt fiber was etched in a hydrochloric acid solution at 45°C for 90 min to increase the surface roughness of the fiber. (3) Grind and sieve the etched basalt fibers, then soak them in a 0.1M ferric chloride solution at 70°C for 8 hours; (4) The basalt fiber obtained in step (3) is soaked in sodium p-toluenesulfonate solution, pyrrole monomer is added and then ferric chloride solution is added. The reaction is carried out at room temperature for 18 hours. The mass ratio of basalt fiber, sodium p-toluenesulfonate, pyrrole monomer and ferric iron is 5.0:10.0:3.8:6.0. (5) The basalt fibers obtained in step (4) were subjected to staged calcination (first stage: low-temperature pre-calcination, heating to 200°C at a rate of 5°C / min, and holding for 30 minutes; second stage: medium-temperature reaction, heating to 400°C at a rate of 3°C / min, and holding for 90 minutes; third stage: high-temperature carbonization, heating to 550°C at a rate of 2°C / min, and holding for 120 minutes) to obtain iron-carbon modified basalt fibers. The porosity of the obtained fibers was 93%, the density was 1.09 g / cm³, and the surface Zeta potential was 15 mV. The porosity originated from the micropore structure formed during the fiber calcination process, and the pore size was mainly nano-sized mesopores (mainly distributed in the range of 10-150 nm).

[0048] Step 2: Preparation of the embedding mixture (1) Weigh 8% polyvinyl alcohol (PVA), 1% sodium alginate (SA), and 0.3% sodium bicarbonate (SB) by mass percentage, and add the remaining extracellular polymeric material (EPS) to a mixed solution of deionized water (volume ratio 1:1). The EPS was obtained by heating (80℃, 2h) the supernatant after anaerobic ammonia oxidation bacteria and centrifuging (8000rpm, 30min). (2) Heat to 96°C in a water bath and stir at 200 rpm to completely dissolve and mix evenly; (3) Cool to 35°C, add the iron-carbon modified basalt fiber prepared in step 1, the amount of which is 5% of the mass of the embedding matrix (PVA+SA), and stir evenly; (4) Take out the sludge from the anaerobic ammonia oxidation reactor that has been running stably in the laboratory for a long time, rinse it repeatedly with phosphate buffer at pH 7.0 three times to remove surface impurities, and collect the bacterial sludge after centrifugation at 4000 rpm for 10 min. (5) Add the fungal mud to the mixture prepared in step (3) (the mass ratio of fungal mud to mixture is 1:6), stir evenly, and obtain the embedding mixture.

[0049] Step 3: Droplet forming and cross-linking curing (1) Preparation of crosslinking solution: Dissolve 1.5% calcium chloride in deionized water according to the mass ratio to obtain the first crosslinking solution; dissolve 4% boric acid, 3% calcium chloride and 1% ferric chloride in deionized water according to the mass ratio, and stir thoroughly to obtain the second crosslinking solution; (2) The embedding mixture is dripped into the first crosslinking liquid in the form of droplets by a peristaltic pump for pre-crosslinking. The dripping rate is controlled so that the particle size of the prepared embedding particles is 4-6 mm. After pre-crosslinking for 10 min, it is transferred to the second crosslinking liquid and crosslinked in a sealed, light-proof environment at 4 °C for 18 h to obtain the embedded particles.

[0050] Step 4: Cleaning and Activation (1) The cross-linked embedded particles were rinsed three times with phosphate buffer (pH 7.0) and deionized water to remove the residual cross-linking solution on the surface; (2) The cleaned embedded particles were placed in a constant temperature incubator and activated at 33°C for 7 days. NH4 was added to the water. + -N and NO2 - With -N concentrations of 20 mg / L, the activity of anaerobic ammonia oxidizing bacteria was restored, resulting in a finished porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia oxidizing bacteria. The specific structure is as follows: Figure 1 As shown.

[0051] Example 2: Preparation of porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia-oxidizing bacteria Step 1: Preparation of iron-carbon modified basalt fiber (MBF) Same as step 1 in Example 1.

[0052] Step 2: Preparation of the embedding mixture (1) Weigh 6% polyvinyl alcohol (PVA), 0.5% sodium alginate (SA), and 0.1% sodium bicarbonate (SB) by mass percentage, and add the remaining extracellular polymeric material (EPS) to a mixed solution of deionized water (volume ratio of 1:1). The EPS was obtained by heating (80℃, 2h) the anaerobic ammonia-oxidizing bacteria and then centrifuging (8000rpm, 30min) to extract the supernatant. (2) Heat to 90°C in a water bath and stir at 200 rpm to completely dissolve and mix evenly; (3) Cool to 30°C, add the iron-carbon modified basalt fiber obtained in step 1, the amount of which is 2% of the mass of the embedding matrix (PVA+SA), and stir evenly; (4) Take out the sludge from the anaerobic ammonia oxidation reactor that has been running stably in the laboratory for a long time, rinse it repeatedly with phosphate buffer at pH 7.0 three times to remove surface impurities, and collect the bacterial sludge after centrifugation at 4000 rpm for 10 min. (5) Add the fungal mud to the mixture prepared in step (3) (the mass ratio of fungal mud to mixture is 1:4), stir evenly, and obtain the embedding mixture.

[0053] Step 3: Droplet forming and cross-linking curing (1) Preparation of crosslinking agent solution: Dissolve 1% calcium chloride in deionized water to obtain the first crosslinking solution; dissolve 3% boric acid, 2% calcium chloride and 0.5% ferric chloride in deionized water and stir thoroughly to obtain the second crosslinking solution; (2) The embedding mixture is dripped into the first crosslinking solution in the form of droplets by a peristaltic pump for pre-crosslinking. The dripping rate is controlled so that the particle size of the prepared embedding particles is 3-5 mm. After 5 min, it is transferred to the second crosslinking solution and crosslinked in a sealed, light-proof environment at 6℃ for 12 h to obtain the embedded particles.

[0054] Step 4: Cleaning and Activation (1) The cross-linked embedded particles were rinsed three times with phosphate buffer (pH 7.0) and deionized water to remove the residual cross-linking solution on the surface; (2) Place the cleaned embedded particles in a constant temperature incubator and activate them at 30℃ for 10 days. Add NH4 in the water. + -N and NO2 - With a concentration of 20 mg / L for each of the -N groups, the activity of anaerobic ammonia oxidizing bacteria was restored, resulting in a finished porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia oxidizing bacteria.

[0055] Example 3: Preparation of porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia-oxidizing bacteria Step 1: Preparation of iron-carbon modified basalt fiber (MBF) Same as step 1 in Example 1.

[0056] Step 2: Preparation of the embedding mixture (1) Weigh 10% polyvinyl alcohol (PVA), 2% sodium alginate (SA), and 0.5% sodium bicarbonate (SB) by mass percentage, and add the remaining extracellular polymeric material (EPS) to a mixed solution of deionized water (volume ratio of 1:1). The EPS was obtained by heating (80℃, 2h) the anaerobic ammonia-oxidizing bacteria and then centrifuging (8000rpm, 30min) to extract the supernatant. (2) Heat to 100°C in a water bath and stir at 200 rpm to completely dissolve and mix evenly; (3) Cool to 40°C, add the iron-carbon modified basalt fiber obtained in step 1, the amount of which is 8% of the mass of the embedding matrix (PVA+SA), and stir evenly; (4) Take out the sludge from the anaerobic ammonia oxidation reactor that has been running stably in the laboratory for a long time, rinse it repeatedly with phosphate buffer at pH 7.0 three times to remove surface impurities, and collect the bacterial sludge after centrifugation at 4000 rpm for 10 min. (5) Add the fungal mud to the mixture prepared in step (3) (the mass ratio of fungal mud to mixture is 1:10), stir evenly, and obtain the embedding mixture.

[0057] Step 3: Droplet forming and cross-linking curing (1) Preparation of crosslinking agent solution: Dissolve 2% calcium chloride in deionized water to obtain the first crosslinking solution; dissolve 5% boric acid, 5% calcium chloride and 2% ferric chloride in deionized water and stir thoroughly to obtain the second crosslinking solution; (2) The embedding mixture is dripped into the first crosslinking solution in the form of droplets by a peristaltic pump for pre-crosslinking. The dripping rate is controlled so that the particle size of the prepared embedding particles is 5-8 mm. After 8 min, it is transferred to the second crosslinking solution and crosslinked in a sealed, light-proof environment at 4℃ for 24 h to obtain the embedded particles.

[0058] Step 4: Cleaning and Activation (1) The cross-linked embedded particles were rinsed three times with phosphate buffer (pH 7.0) and deionized water to remove the residual cross-linking solution on the surface; (2) Place the cleaned embedded particles in a constant temperature incubator and activate them at 35°C for 14 days. Add NH4 in the water. + -N and NO2 - With a concentration of 20 mg / L for each of the -N groups, the activity of anaerobic ammonia oxidizing bacteria was restored, resulting in a finished porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia oxidizing bacteria.

[0059] Comparative Example 1 (with pore formation + without MBF) Step 1: Preparation of iron-carbon modified basalt fiber (MBF) Same as step 1 in Example 1.

[0060] Step 2: Preparation of the embedding mixture (1) Weigh 8% polyvinyl alcohol (PVA), 1% sodium alginate (SA), and 0.3% sodium bicarbonate (SB) by mass percentage, and add the remaining extracellular polymeric material (EPS) to a mixed solution of deionized water (volume ratio of 1:1). The EPS was obtained by heating (80℃, 2h) the anaerobic ammonia oxidizing bacteria and then centrifuging (8000rpm, 30min) to extract the supernatant. (2) Heat to 96°C in a water bath and stir at 200 rpm to completely dissolve and mix evenly; (3) Cool to 35°C (without adding iron-carbon modified basalt fiber) to obtain a mixture; (4) Take out the sludge from the anaerobic ammonia oxidation reactor that has been running stably in the laboratory for a long time, rinse it repeatedly with phosphate buffer at pH 7.0 three times to remove surface impurities, and collect the bacterial sludge after centrifugation at 4000 rpm for 10 min. (5) Add the fungal mud to the mixture prepared in step (3) (the mass ratio of fungal mud to mixture is 1:6), stir evenly, and obtain the embedding mixture.

[0061] Step 3: Droplet forming and cross-linking curing (1) Preparation of crosslinking solution: Dissolve 1.5% calcium chloride in deionized water according to the mass ratio to obtain the first crosslinking solution; dissolve 4% boric acid, 3% calcium chloride and 1% ferric chloride in deionized water according to the mass ratio, and stir thoroughly to obtain the second crosslinking solution; (2) The embedding mixture is dripped into the first crosslinking liquid in the form of droplets by a peristaltic pump for pre-crosslinking. The dripping rate is controlled so that the particle size of the prepared embedding particles is 4-6 mm. After pre-crosslinking for 10 min, it is transferred to the second crosslinking liquid and crosslinked in a sealed, light-proof environment at 4 °C for 18 h to obtain the embedded particles.

[0062] Step 4: Cleaning and Activation (1) The cross-linked embedded particles were rinsed three times with phosphate buffer (pH 7.0) and deionized water to remove the residual cross-linking solution on the surface; (2) The cleaned embedded particles were placed in a constant temperature incubator and activated at 33°C for 7 days. NH4 was added to the water. + -N and NO2 - With a concentration of 20 mg / L for each of the -N groups, the activity of anaerobic ammonia oxidizing bacteria was restored, resulting in a finished porous PVA-SA composite biological packing material for embedding anaerobic ammonia oxidizing bacteria.

[0063] Comparative Example 2 (No pore formation + with MBF) Step 1: Preparation of iron-carbon modified basalt fiber (MBF) Same as step 1 in Example 1.

[0064] Step 2: Preparation of the embedding mixture (1) Weigh 8% polyvinyl alcohol (PVA) and 1% sodium alginate (SA) by mass percentage, without adding sodium bicarbonate, and add the remaining extracellular polymeric material (EPS) to a mixed solution of deionized water (volume ratio of 1:1). The EPS was obtained by heating (80℃, 2h) with anaerobic ammonia-oxidizing bacteria and then centrifuging (8000rpm, 30min) to extract the supernatant. (2) Heat to 96°C in a water bath and stir at 200 rpm to completely dissolve and mix evenly; (3) Cool to 35°C, add the iron-carbon modified basalt fiber obtained in step 1 to obtain a mixture, the amount added is 5% of the mass of the embedding matrix (PVA+SA), and stir evenly. (4) Take out the sludge from the anaerobic ammonia oxidation reactor that has been running stably in the laboratory for a long time, rinse it repeatedly with phosphate buffer at pH 7.0 three times to remove surface impurities, and collect the bacterial sludge after centrifugation at 4000 rpm for 10 min. (5) Add the fungal mud to the mixture prepared in step (3) (the mass ratio of fungal mud to mixture is 1:6), stir evenly, and obtain the embedding mixture.

[0065] Step 3: Droplet forming and cross-linking curing (1) Preparation of crosslinking solution: Dissolve 1.5% calcium chloride in deionized water according to the mass ratio to obtain the first crosslinking solution; dissolve 4% boric acid, 3% calcium chloride and 1% ferric chloride in deionized water according to the mass ratio, and stir thoroughly to obtain the second crosslinking solution; (2) The embedding mixture is dripped into the first crosslinking liquid in the form of droplets by a peristaltic pump for pre-crosslinking. The dripping rate is controlled so that the particle size of the prepared embedding particles is 4-6 mm. After pre-crosslinking for 10 min, it is transferred to the second crosslinking liquid and crosslinked in a sealed, light-proof environment at 4 °C for 18 h to obtain the embedded particles.

[0066] Step 4: Cleaning and Activation (1) The cross-linked embedded particles were rinsed three times with phosphate buffer (pH 7.0) and deionized water to remove the residual cross-linking solution on the surface; (2) The cleaned embedded particles were placed in a constant temperature incubator and activated at 33°C for 7 days. NH4 was added to the water. + -N and NO2 - With a concentration of 20 mg / L for each of the -N groups, the activity of anaerobic ammonia oxidizing bacteria was restored, resulting in the finished product, a PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia oxidizing bacteria.

[0067] Comparative Example 3 (No pore formation + No MBF) Step 1: Preparation of the embedding mixture (1) Weigh out 8% polyvinyl alcohol (PVA) and 1% sodium alginate (SA) by mass percentage, without adding sodium bicarbonate, and add the remainder to deionized water; (2) Heat to 96°C in a water bath and stir at 200 rpm to completely dissolve and mix evenly; (3) Cool to 35°C (without adding iron-carbon modified basalt fiber) to obtain a mixture; (4) Take out the sludge from the anaerobic ammonia oxidation reactor that has been running stably in the laboratory for a long time, rinse it repeatedly with phosphate buffer at pH 7.0 three times to remove surface impurities, and collect the bacterial sludge after centrifugation at 4000 rpm for 10 min. (5) Add the fungal mud to the mixture prepared in step (3) (the mass ratio of fungal mud to mixture is 1:6), stir evenly, and obtain the embedding mixture.

[0068] Step 2: Droplet forming and cross-linking curing (1) Preparation of crosslinking solution: Dissolve 1.5% calcium chloride in deionized water according to the mass ratio to obtain the first crosslinking solution; dissolve 4% boric acid, 3% calcium chloride and 1% ferric chloride in deionized water according to the mass ratio, and stir thoroughly to obtain the second crosslinking solution; (2) The embedding mixture is dripped into the first crosslinking liquid in the form of droplets by a peristaltic pump for pre-crosslinking. The dripping rate is controlled so that the particle size of the prepared embedding particles is 4-6 mm. After pre-crosslinking for 10 min, it is transferred to the second crosslinking liquid and crosslinked in a sealed, light-proof environment at 4 °C for 18 h to obtain the embedded particles.

[0069] Step 4: Cleaning and Activation (1) The cross-linked embedded particles were rinsed three times with phosphate buffer (pH 7.0) and deionized water to remove the residual cross-linking solution on the surface; (2) The cleaned embedded particles were placed in a constant temperature incubator and activated at 33°C for 7 days. NH4 was added to the water. + -N and NO2 - With a concentration of 20 mg / L for each of the -N groups, the activity of anaerobic ammonia oxidizing bacteria was restored, resulting in the finished product, PVA-SA composite biological packing material for embedding anaerobic ammonia oxidizing bacteria.

[0070] The physicochemical properties of the biological packing materials prepared in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1 below. Table 1. Physicochemical properties of biological packing materials in different embodiments and comparative examples. Note: The relative mass transfer coefficient is based on Comparative Example 3 (traditional PVA-SA dense embedding) with a value of 1.0. A higher value indicates better mass transfer performance. As can be seen from the table above, a single-pore structure cannot simultaneously achieve both strength and mass transfer. Comparative Example 1, relying solely on macroscopic pores for mass transfer, achieved a 2.8-fold increase in strength compared to a dense structure, but the mechanical strength dropped to 1050g, making the particles prone to breakage in practical use. Comparative Example 2, relying solely on MBF micropores, achieved a strength of 1950g, but the mass transfer only increased by 1.6 times, and the mass transfer resistance problem caused by the PVA dense layer was not resolved. The three examples employed a dual-pore structure with both macroscopic foamed pores and MBF mesopores, achieving a relative mass transfer coefficient of 3.8-4.6 times, while maintaining a mechanical strength within the range of 1700-2000g, indicating that strength and mass transfer can be balanced. The role of MBF is that the fibers act as bridges and prevent breakage within the particles, compensating for the strength loss caused by the porous structure. Within the addition range of 2% to 8%, appropriately increasing the MBF dosage improves both strength and mass transfer, with Example 3 achieving the highest values ​​for both (2000g strength and 4.6 times mass transfer). The results of Comparative Examples 1 and 2 further illustrate that MBF enhancement and macroporation are both indispensable; the level of the embodiments cannot be achieved without either one.

[0071] Example 4: Construction of an anaerobic ammonia oxidation biological filter suitable for high-salt nitrogen wastewater and treatment of simulated high-salt nitrogen wastewater. The biological packing materials prepared in Examples 1-3 and Comparative Examples 1-3 were respectively filled into anaerobic ammonia oxidation biological filters to investigate their denitrification performance in the treatment of simulated high-salt nitrogen-containing wastewater.

[0072] 1. Experimental setup An upflow biological filter was used as the anaerobic ammonia oxidation reactor. The reactor body was made of plexiglass, with an effective volume of 5L and a height-to-diameter ratio of 5:1. Figure 2 As shown, the reactor has an inlet system and an aeration system (used only for removing dissolved oxygen and shut off during operation) at the bottom, and an outlet system at the top. The biological packing materials prepared in Examples 1-3 and Comparative Examples 1-3 were respectively filled into the reactor, with a volume filling ratio of 30%. Heating belts were wrapped around the outside of the reactor, and the reaction temperature was controlled by a temperature controller.

[0073] 2. Influent water quality Simulated high-salt, nitrogen-containing wastewater, with the following influent water quality: NH4 + -N: 100-200 mg / L; NO2 - -N: 132-264 mg / L (as NH4) + -N:NO2 - -N=1:1.32 (addition). NaCl: 10-35 g / L (simulating a high-salinity environment); The rest is made with tap water, with the pH adjusted to 7.5-8.0.

[0074] 3. Operating parameters (1) Temperature control: 33±1℃ (maintained by heating belt and temperature controller); (2) pH control: 7.5-8.0 (adjusted by adding NaHCO3 to the influent, and monitored and manually adjusted daily); (3) Hydraulic retention time (HRT): 12h (the inlet flow rate is controlled by a peristaltic pump); (4) Dissolved oxygen (DO): <0.1mg / L, maintaining an anaerobic environment (the influent is stripped with nitrogen for 30 min to remove dissolved oxygen, and the top of the reactor is sealed). (5) Operation cycle: Continuous operation, with daily sampling and testing of effluent water quality.

[0075] 4. Analysis Items and Methods Test items, test methods, and test frequency: NH4 + -N: Nessler's reagent spectrophotometry, once daily; NO2 - -N:N-(1-naphthyl)-ethylenediamine spectrophotometry, once daily; NO3 - -N: Ultraviolet spectrophotometry, once daily; TN: Potassium persulfate oxidation-ultraviolet spectrophotometry, once every 3 days; pH: pH meter, twice daily; 5. Effectiveness Evaluation (1) Calculate the NH4 in each reactor separately. + -N removal rate, NO2 - -N removal rate, total nitrogen (TN) removal rate and stoichiometric ratio (ΔNH4) + -N:ΔNO2 - -N:ΔNO3 - The nitrogen removal performance of the biological packing material in each embodiment was evaluated by comparing the nitrogen content (-N) with the theoretical value (1:1.32:0.26). (2) Observe the start-up rate of each reactor (using NH4) + -N removal rate stably reaches over 80% (time required). (3) Observe the integrity, breakage rate and floating of the embedded particles during operation, and evaluate their mechanical strength and operational stability; 6. Experimental Results Specific data are shown in Table 2, where... (1) Example 1: NH4 + -N removal rate 96%, NO2 --N removal rate 97%, TN removal rate 93%, start-up period of about 10 days, particle integrity rate 97%, strong resistance to salt shock. (2) Example 2: NH4 + -N removal rate 92%, NO2 - -N removal rate 93%, TN removal rate 91%, start-up period of about 14 days, particle integrity rate 94%, strong resistance to salinity shock. (3) Example 3: NH4 + -N removal rate 94%, NO2 - -N removal rate 95%, TN removal rate 92%, start-up period of about 12 days, particle integrity rate 96%, strong resistance to salinity shock. (4) Comparative Example 1 (with pore formation + without MBF): NH4 + -N removal rate 82%, NO2 - -N removal rate 84%, TN removal rate approximately 79%, start-up period approximately 22 days, particle integrity rate approximately 88%; (5) Comparative Example 2 (no pore formation + with MBF): NH4 + -N removal rate is approximately 78%, NO2 - -N removal rate 80%, TN removal rate approximately 75%, start-up period approximately 28 days, particle integrity rate 91%; (6) Comparative Example 3 (no pore formation + no MBF, conventional PVA-SA): NH4 + -N removal rate is approximately 67%, NO2 - -N removal rate is 60%, TN removal rate is approximately 60%, start-up period is 45 days, and particle integrity rate is approximately 83%. Table 2. Denitrification effect of biological packing material in different embodiments and comparative examples. It is evident that, under the same influent conditions and operating parameters, after 60 days of operation, the technical solution of this application is significantly superior to the comparative examples in terms of denitrification efficiency, particle mechanical strength, anti-buoyancy performance, and salt tolerance.

[0076] Example 5: Treatment of High-Salinity, Nitrogenous Actual Wastewater High-salinity nitrogen-containing actual wastewater was introduced into the anaerobic ammonia oxidation biological filter of Example 4 for denitrification treatment. The hydraulic retention time was 12 hours, and the water temperature was maintained at 33℃±1℃. Wastewater parameters: NH4 + -N 100-200mg / L, NO2 - -N 100-260mg / L, NaCl 25-35g / L.

[0077] Testing showed that during 30 days of stable operation after treatment, this application significantly improved the removal efficiency of nitrite and ammonia nitrogen in actual wastewater with different sodium chloride concentrations. The ammonia nitrogen removal rate exceeded 92%, the nitrite nitrogen removal efficiency exceeded 93%, and the total nitrogen removal rate exceeded 91%. Therefore, the porous PVA-SA-MBF composite biological packing material with embedded anaerobic ammonia oxidizing bacteria prepared in this application can effectively treat nitrogen-containing industrial wastewater with a salinity of up to 35 g / L, and is suitable for treating high-salt and complex wastewater, thus expanding the application scope of the anaerobic ammonia oxidation process.

[0078] The above embodiments are merely illustrative of the principles and effects of this application and are not intended to limit this application. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of this application. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in this application should still be covered by the claims of this application.

Claims

1. A method for preparing a porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia-oxidizing bacteria, characterized in that, Includes the following steps: S a Preparation of iron-carbon modified basalt fiber (MBF); S b Preparation of embedding mixture S b 1. Weigh out 6%-10% polyvinyl alcohol (PVA), 0.5%-2% sodium alginate (SA), 0.1%-0.5% sodium bicarbonate (SB), and the remainder of an aqueous solution of extracellular polymeric substances (EPS) by mass percentage. S b 2. Step S b The substance weighed in step 1 is stirred and heated to 90-100℃ to dissolve; S b 3. Cool to 30-40℃, then add step S. a The iron-carbon modified basalt fiber MBF obtained in the process was mixed with a solution, and the amount of iron-carbon modified basalt fiber MBF added was 2%-8% of the total mass of polyvinyl alcohol (PVA) and sodium alginate (SA). S b 4. Add the pretreated sludge to step S. b 3. An embedded mixed solution is obtained from the prepared mixture, wherein the mass ratio of the pretreated bacterial mud to the mixed solution is 1:4-10; S c Droplet molding and cross-linking curing S c 1. Dissolve 1%-2% calcium chloride in deionized water according to the mass ratio to obtain the first crosslinking solution; dissolve 3%-5% boric acid, 2%-5% calcium chloride and 0.5%-2% ferric chloride in deionized water according to the mass ratio to obtain the second crosslinking solution; S c 2. After pre-crosslinking the embedding mixture in the first crosslinking solution for 5-10 minutes, transfer it to the second crosslinking solution and crosslink it in a sealed, light-protected environment at 4-10℃ for 12-24 hours to obtain the embedded particles. S d Cleaning and activation After cleaning, the embedded particles were placed in a constant temperature incubator and activated at 30-35℃ for 7-14 days to obtain the porous PVA-SA-MBF composite biological packing material containing anaerobic ammonia oxidizing bacteria.

2. The preparation method according to claim 1, characterized in that, Step S a include: S a 1. After pretreatment and etching, the basalt fibers are ground and sieved, then soaked in an iron salt solution for 6-12 hours at a temperature of 50-90℃. S a 2. Step S a The obtained basalt fibers were soaked in sodium p-toluenesulfonate solution, followed by the addition of pyrrole monomer and then iron salt solution. The reaction was carried out at room temperature for 12-24 h. The mass ratio of basalt fibers, sodium p-toluenesulfonate, pyrrole monomer and ferric iron was 5.0:9.7-10.8:3.4-4.2:5.5-6.

6. S a 3. The basalt fibers obtained in step S2 are calcined in stages, wherein... First stage: Raise the temperature to 180-220°C and maintain the temperature for 25-40 minutes. Second stage: Raise the temperature to 350-400°C and maintain the temperature for 80-100 minutes. Third stage: Raise the temperature to 510-560°C and keep it warm for 100-130 minutes.

3. The preparation method according to claim 1, characterized in that, The extracellular polymeric substance (EPS) aqueous solution was prepared by mixing the extracellular polymeric substance (EPS) with deionized water at a volume ratio of 1:

1. The extracellular polymeric substance (EPS) was the supernatant extracted by centrifugation after heating anaerobic ammonia-oxidizing bacteria.

4. The preparation method according to claim 1, characterized in that, Step S c 2 also includes controlling the dropping rate to ensure that the particle size of the prepared embedded particles is 3-8 mm.

5. A porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia-oxidizing bacteria, prepared by the method described in any one of claims 1-4, characterized in that, include: Embedding matrix: a composite gel of polyvinyl alcohol (PVA) and sodium alginate (SA); Iron-carbon modified basalt fiber (MBF): dispersed in the embedded matrix; Anaerobic ammonia-oxidizing bacteria: embedded in the embedding matrix.

6. The porous PVA-SA-MBF composite biological packing material for embedding anaerobic ammonia-oxidizing bacteria according to claim 5, characterized in that, The iron-carbon modified basalt fiber has a porosity of 90%-93%, a density of 1.03-1.15 g / cm³, and a surface Zeta potential of 10-20 mV.

7. A method for constructing an anaerobic ammonia oxidation biological filter suitable for high-salt nitrogen-containing wastewater, characterized in that, include: The porous PVA-SA-MBF composite biological packing material containing anaerobic ammonia oxidizing bacteria as described in claim 5 or 6 is filled into an anaerobic ammonia oxidizing biological filter, wherein the anaerobic ammonia oxidizing biological filter is an upflow biological filter, and the volume filling ratio of the porous PVA-SA-MBF composite biological packing material containing anaerobic ammonia oxidizing bacteria is 20%-50%.

8. An anaerobic ammonia oxidation biological filter suitable for high-salt nitrogen-containing wastewater, characterized in that, Constructed using the construction method described in claim 7.

9. The application of the porous PVA-SA-MBF composite biological packing material for encapsulating anaerobic ammonia-oxidizing bacteria as described in claim 5 or 6, or the anaerobic ammonia-oxidizing biological filter suitable for high-salt nitrogen-containing wastewater as described in claim 8, in the treatment of high-salt nitrogen-containing wastewater, wherein, The sodium chloride content in the high-salt nitrogen-containing wastewater is 10-35 g / L.

10. A method for treating high-salt, nitrogen-containing wastewater, characterized in that, include: The high-salt nitrogen-containing wastewater is fed into the anaerobic ammonia oxidation biological filter for high-salt nitrogen-containing wastewater as described in claim 8, and the operating temperature is controlled at 25-35℃, the pH at 7.2-8.5, and the hydraulic retention time at 8-12h.

Citation Information

Patent Citations

  • Iron-carbon modified basalt fiber particle electrode biological carrier as well as preparation method and application thereof

    CN120398262A